Method and apparatus for optical polarization photon generator - Mohd Zain, Mohd Norzaliman; ,, Suryadi; Saharudin, Suhairi; Khir, Mohd Fared Abdul; YUSOF, Zalhan Md; Wahiddin, Mohamed Ridza (2011)
A method and apparatus for optically generating polarized photons with at least four polarization states is disclosed. The method and apparatus comprises at least two laser sources that are electronically triggered at random to generate at least two optical pulses (102), an arrangement of passive optical components that polarize each optical pulse of the at least two optical pulses to have orthogonal polarization states (104) and merge the at least two optical pulses having orthogonal polarization states onto a single optical path (106) and an active optical component that alters the orthogonal polarization states of the single optical path to have secondary orthogonal polarization states (108).